Cone-beam computed tomographic analysis of maxillary sinus septa among Yemeni population: a cross-sectional study - Bassam A. Altayar; Barakat Al-Tayar; Weimin Lin; Saddam N. Al-wesabi; Eissa A. Al-shujaa; Karim Sakran; Quan Yuan; Mingyue Lyu (BMC, 2023)
Abstract Background Maxillary sinus septa increase perforation risk of Schneiderian membrane during the sinus floor elevation (SFE). Cone Beam Computed Tomography (CBCT) allows for a more precise assessment of the septal position; thus, preoperative CBCT analysis is substantial to avoid possible complications. This study aims to investigate the 3D characteristics of the maxillary sinus septa based on CBCT images. To our knowledge, no study reported the CBCT-based investigation for the sinus septa among Yemeni population. Materials and methods This is a retrospective cross-sectional analysis of 880 sinus CBCT images 440 patients. The septa prevalence, locations, orientations, morphology, and associated factors were analyzed. The effect of age, gender, and dental status on the sinus septa and the relationship between sinus membrane pathology and sinus septa were also analyzed. Anatomage (Invivo version 6) was used for CBCT images analysis. Descriptive and analytical statistics were performed, and a P-value < 0.05 was significantly considered. Results The maxillary sinus septa were found among 63.9% of patients and 47% of sinuses. The average septa height was 5.2 mm. 15.7% of patients had septa in the right maxilla, 18% in the left, and 30.2% in both. Gender, age, and dental condition had no influence on the presence of septa, and septa presence did not influence sinus membrane pathology. Many septa originated from the floor (54.5%), located in the middle (43%), with coronal orientation (66%) and complete configuration (58.2%). Conclusion Based on our findings, the septa prevalence, locations, orientations, and morphology were significant and equivalent to the highest recorded in the literature yet. Thus, when sinus floor elevation is planned, CBCT imaging of the maxillary sinus is recommended for safe dental implantation.